2016
DOI: 10.1002/ece3.2606
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence patterns in a diverse arboreal ant community are explained more by competition than habitat requirements

Abstract: A major goal of community ecology is to identify the patterns of species associations and the processes that shape them. Arboreal ants are extremely diverse and abundant, making them an interesting and valuable group for tackling this issue. Numerous studies have used observational data of species co‐occurrence patterns to infer underlying assembly processes, but the complexity of these communities has resulted in few solid conclusions. This study takes advantage of an observational dataset that is unusually w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 83 publications
(121 reference statements)
3
37
0
Order By: Relevance
“…We argue that the historical component is indeed important, however it must be coupled with the influence of recent ecological conditions inherent from the surrounding vegetation domains, such nesting site availability and colony establishment (e.g. Guimarães et al 2007, Andersen 2008), as well as species interactions outcomes (Cerdá et al 2013, Camarota et al 2016), which are likely to be responsible for the compositional uniqueness we observed in the ant community among vegetation domains.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We argue that the historical component is indeed important, however it must be coupled with the influence of recent ecological conditions inherent from the surrounding vegetation domains, such nesting site availability and colony establishment (e.g. Guimarães et al 2007, Andersen 2008), as well as species interactions outcomes (Cerdá et al 2013, Camarota et al 2016), which are likely to be responsible for the compositional uniqueness we observed in the ant community among vegetation domains.…”
Section: Discussionmentioning
confidence: 82%
“…At the local scale, interspecific interactions (e.g. competition, mutualism), resource availability, and environmental variables are often described as the major drivers of ant community structure (Srivastava 1999, Baccaro et al 2012, Camarota et al 2016. Examples of environmental variables include tree richness, height, and abundance (Ribas et al 2003, Klimes et al 2012, Sousa-Souto et al 2016, variation in canopy coverage (Neves et al 2013), and characteristics of soil structure (Schmidt et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…) or species interactions (Blüthgen and Stork , Camarota et al. ), also significantly influence arboreal ant community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other ecological factors, such as competition (Camarota et al. ), might play a larger role than habitat limitations in shaping ant communities in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Although basal area is an effective proxy for tree size in other systems (O'Brien et al 1995), as trees grow in the floating marsh, the added weight causes them to sink deeper into the floating mat creating inconsistencies between dbh and root area. Alternatively, other ecological factors, such as competition (Camarota et al 2016), might play a larger role than habitat limitations in shaping ant communities in this system.…”
Section: Discussionmentioning
confidence: 99%